Using Blockchain Technology to Promote Energy Sustainability in Cities (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research examines the use of blockchain technology to support energy sustainability in urban areas. Blockchain offers transparency, security, and efficiency in recording and distributing energy data, potentially optimizing renewable energy use and reducing carbon emissions. The research method involves literature analysis and simulations of blockchain applications in urban energy systems. The results show that blockchain implementation can increase energy distribution efficiency by up to 20%, reduce data reporting time by up to 99%, and reduce carbon emissions by 50%. In conclusion, blockchain technology can be a strategic innovation in supporting the transition to a sustainable and environmentally friendly energy system.